Broadband planar dipole array Antenna with double C-shaped slit elements for digital TV broadcasting transmission - Osklang, Pracha; Phongcharoenpanich, Chuwong (My University, 2016)
This research has proposed a planar rectangular dipole antenna enclosed in double C-shaped parasitically slit elements (i.e., radiator element) on a double-cornered reflector for bandwidth enhancement. In the study, simulations were first carried out to determine the optimal parameters of the radiator element and then a radiator element prototype was fabricated and mounted onto a double-cornered aluminum reflector. The simulated and measured |S11|<–10 dB of the antenna element covered the frequency ranges of 451–901 MHz (66.6%) and 455–886 MHz (64.3%), respectively. The gain was enhanced by the subsequent deployment of multiple radiator elements to fabricate a four-element vertically array antenna on an elongated double-cornered reflector. The simulated and measured |S11|<−10 dB of the array antenna, respectively, covered the 410–991 MHz (82.9%) and 415–886 MHz (72.4%) frequency ranges. The proposed array antenna radiates unidirectionally across the DTV frequency band with a measured front-to-back ratio and cross polarization >20 and <−23 dB, respectively. The simulated and measured half-power beam widths in the E and H planes were respectively 56° ± 13° and 20° ± 6°; and 57° ± 13° and 21° ± 6°. In addition, the simulated and measured gains of the array antenna were 12.8–16.4 dBi and 11.3–15.8 dBi along the 470–862 MHz frequency range. This proposed array antenna is thus suitable for DTV broadcasting transmission. © 2016 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:466–478, 2016.
Keywords: array antenna; broadband antenna; C-shaped slit; DTV